Inelastic Response of Soil-Pile-Structure Interaction System under Lateral Loading: A Parametric Study - Sekhri, Khadidja; Yahiaoui, Djarir; Abbeche, Khelifa (Jordan Journal of Civil Engineering, 2020)
Soil-structure interaction is the key to study the behavior of structures under static or dynamic loading. The pile foundation is adopted to transfer loads from the structure to the soil when the structure is embedded in a weak soil stratum. Soil-pile system has a nonlinear behavior; thus, it is more complicated to understand. This study focuses on the numerical investigation of interaction of soil–pile–structure system (ISPS) and interaction of soil–pile system (ISP) under lateral loads. Nonlinear static analysis is carried out considering the lateral capacity of ISPS and ISP systems under lateral loading using pushover analysis. A parametric study concerning different types of axial loading, pile length and pile radius, as well as longitudinal steel ratio in different types of sand is conducted to observe the response of (ISPS) and (ISP) systems. Besides that, lateral capacity deflection and moment curves, as well as the formation of plastic hinge are evaluated for ISPS and ISP systems for a typical pile and various soil types and their results are presented. The results show that the lateral capacity is influenced by the parametric study.